Phenotypic and transcriptomic responses of the shade-grown species Panax ginseng to variable light conditions. (13th August 2022) - Zhang, Yu-Xin; Niu, Yu-Qian; Wang, Xin-Feng; Wang, Zhen-Hui; Wang, Meng-Li; Yang, Ji; Wang, Yu-Guo; Zhang, Wen-Ju; Song, Zhi-Ping; Li, Lin-Feng
Abstract: Background and Aims: Elucidating how plant species respond to variable light conditions is important to understand the ecological adaptation to heterogeneous natural habitats. Plant performance and its underlying gene regulatory network have been well documented in sun-grown plants. However, the phenotypic and molecular responses of shade-grown plants under variable light conditions have remained largely unclear. Methods: We assessed the differences in phenotypic performance between Panax ginseng (shade-grown) and Arabidopsis thaliana (sun-grown) under sunlight, shade and deep-shade conditions. To further address the molecular bases underpinning the phenotypic responses, we compared time-course transcriptomic expression profiling and candidate gene structures between the two species. Key Results: Our results show that, compared with arabidopsis, ginseng plants not only possess a lower degree of phenotypic plasticity among the three light conditions, but also exhibit higher photosynthetic efficiency under shade and deep-shade conditions. Further comparisons of the gene expression and structure reveal that differential transcriptional regulation together with increased copy number of photosynthesis-related genes (e.g. electron transfer and carbon fixation) may improve the photosynthetic efficiency of ginseng plants under the two shade conditions. In contrast, the inactivation of phytochrome-interacting factors (i.e. absent and no upregulation of the PIF genes) are potentially associated with the observed low degree of phenotypic plasticity of ginseng plants under variable light conditions. Conclusions: Our study provides new insights into how shade-grown plants respond to variable light conditions. Candidate genes related to shade adaptation in ginseng provide valuable genetic resources for future molecular breeding of high-density planting crops.